2018
DOI: 10.1002/adfm.201802506
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Recording and Hierarchical Surface Patterning on Periodic Submicrometer Pillar Arrays of Azo Molecular Glass via Polarized Light Irradiation

Abstract: Periodic submiocrometer pillar arrays are fabricated from a photoresponsive azo molecular glass (IA-Chol) by soft-lithographic hot embossing with elastomeric poly(dimethylsiloxane) (PDMS) modes. Through deformation of each submicrometer-sized pillar in response to the local amplitude and polarization of the superimposed electric waves, optical holograms are recorded on the IA-Chol pillar arrays. When the interference pattern is formed by two polarized beams with opposite-circular polarizations, the recorded pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Thus far, a sub‐30 nm structural pattern has been produced with photoisomerization‐driven directional mass migration of azomaterials . This resolution is comparable to that of current semiconducting technologies, such as extreme UV lithography and directed self‐assembly . Additionally, photochromic NSOM imaging can guarantee a resolution of a few nanometers, exceeding that of scattering‐based conventional NSOM .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus far, a sub‐30 nm structural pattern has been produced with photoisomerization‐driven directional mass migration of azomaterials . This resolution is comparable to that of current semiconducting technologies, such as extreme UV lithography and directed self‐assembly . Additionally, photochromic NSOM imaging can guarantee a resolution of a few nanometers, exceeding that of scattering‐based conventional NSOM .…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al reported another promising application of the directional mass migration of azomaterials for advancing metasurfaces, as shown in Figure . Pristine nanoscale, azomaterial posts, which are regular arrays over a large area, can be individually reconfigured into a graded unit array by a one‐shot illumination with an interference pattern (Figure a–f).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By exploiting the directional mass transfer feature, SRGs have been efficiently inscribed on the azo polymer films by using the interfering CPL with opposite circulations . To be utilized for such applications, amorphous molecular materials containing azo chromophores (azo molecular glasses) show some unique advantages, such as well‐defined structures, high chromophore density, easy purification, no chain entanglements of polymers, and good processibility . Although molecular weights are much lower than those of their polymeric counterparts, azo molecular glasses can be feasibly used to prepare optical quality solid films, which are highly stable for storage in the glassy state below glass transition temperature ( T g ) .…”
Section: Introductionmentioning
confidence: 99%